Cultural Literacy Management Strategy: Increasing Multicultural Awareness in Primary Schools - Awalla, Afra Ilmi Taqrir; Nisa, Choirun (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The aim of this research is to find out about cultural literacy at SD Negeri Wonotolo 3, Sragen Regency, and how it is managed through superior programs to enhance multicultural awareness. Methodology: This research uses a qualitative approach. Data collection techniques include observation, interviews, and documentation. Results: The findings show that cultural literacy management through superior programs at SDN Wonotolo 3 effectively increases multicultural awareness. (1) Planning is carried out by the school’s Cultural Team, which formulates objectives and identifies the school's potential. (2) Organizing involves structuring resources and defining roles to implement cultural literacy programs effectively. (3) Monitoring is conducted regularly or irregularly, involving various stakeholders, especially the Culture Team. (4) Obstacles faced include the diversity of student characteristics and limited funding. (5) Implementation of a quality cultural program has resulted in achievements by students, teachers, principals, and the school institution at sub-district, district, provincial, and national levels. Applications/Originality/Value: This study provides insights into how structured cultural literacy programs can foster multicultural awareness in primary schools. It also highlights practical strategies for planning, organizing, and monitoring such initiatives in resource-limited settings.